Efektivitas ekstrak etanol daun ungu (Gratophyllum pictum (L.)) untuk menurunkan kadar TNF-Î± dan NO - Nur Patria Tjahjani; Tri Nur Kristina; Endang Sri Lestari (Universitas Ahmad Dahlan, 2016)
Ethanol extract of Gratophyllum pictum L (G. pictum L). leaves contain phytochemical compounds such as alkaloids, tannins and flavonoids, which have antibacterial activity against Staphylococcus aureus. This study aims to prove the effectiveness ofÂ ethanol extract ofÂ G. pictum L. to reduce the level of TNF-Î± and NO in Swiss mice infected with S. aureus.The study treated 30 Swiss mice divided into 5 groups, consist of: K (-) normal mice ; K (+) mice were infected with S. aureus ; P1, P2, P3 were infected with S. aureus and given the ethanol extract of G. pictum leaves,75,150, and 300 mg/kgBW/day for 7 days . Mean levels of TNF-Î± of group K(-), K (+), P1, P2, P3 were 300.29; 550.29; 390.34; 517.67; 327.55 pg / mL respectively. One Way ANOVA test showed that there were significant differences between all treatment groups (p = 0.001), LSD Post Hoc test revealed P1 and P3 groups different significantly with K (+) with p= 0.013 and p = 0.001. Mean levels of NO of group K (-), K (+), P1, P2, P3 were 1.32; 3.56; 2.50; 2.64; and 1.56 Î¼M/mL respectively. Kruskal WallisTest showed that the levels of NO not significantly different, although NO levels at 300 mg/kgBW/day similar with to the levels of NO group K(-). Spearman correlation test showed that there were correlations between TNF-Î± and NO with the variation results on each treatment groups. Ethanol extract ofÂ G. pictum leaves at 300 mg/kgBW/day for 7 days is regarded as the effective dose to reduce TNF-Î± and NO levels in Swiss mice infected by S. aureus.